New Approach for Modeling Start‐up, Shutdown, and Malfunction Emissions. Issue 2 (13th August 2018) - Warren, Christopher; Paine, Robert
Abstract : The ability to account for unplanned high‐emission spikes or events is not readily available through the use of the US Environmental Protection Agency's (EPA's) guideline models, such as AERMOD.